Religious rights to wear headscarf: Indonesian and Malaysian’s Constitutional Court’s perspective - Adhani, Hani; Rachminawati, Rachminawati; Mokhtar, Khairil Azmin (2019)
A modern constitution safeguards human rights. Although the views on human rights in each country are different, it has been generally agreed that one of the rights is freedom of religion. Accordingly, the Indonesian Constitution (UUD 1945) proclaims freedom of religion in Article 28E which states, "The State guarantees the freedom of every citizen to embrace his or her religion and to worship according to his religion and belief". Also in the Malaysian Constitution, article 11 states that every person has the right to profess, practice and propagate religion. One of the controversies relating to freedom of religion is the prohibition of hijab for Muslim women which occurred in several countries in the world. This research elaborates the correlation between religious freedom and the right to dress according to one’s religion as governed under the Indonesian dan Malaysian constitutions. The study also examines rules governing religious freedom especially freedom of religious attire from various sources such as international human rights conventions, declarations and laws.